Environmental management practices, operational competitiveness and environmental performance: Empirical evidence from a developing country. Issue 3 (16th April 2018) - Famiyeh, Samuel; Adaku, Ebenezer; Amoako-Gyampah, Kwasi; Asante-Darko, Disraeli; Amoatey, Charles Teye
Abstract : Purpose: The purpose of this paper is to examine the relationship between environmental management practices (EMP) and competitive operational performance with respect to reduced cost, improved quality, improved flexibility and improved delivery as well as overall environmental performance, of firms, using data from a developing country. Design/methodology/approach: The study employed a survey approach with responses from 164 informants from different industries and used partial least squares structural equation modeling to examine the relationship between EMP and competitive operational performance and their overall impact on the environmental performance of firms. Findings: The results indicate that EMP by firms have a significant positive effect on firms' competitive operational performance. Again, firms' competitive operational performance has a partial positive effect on the overall environmental performance. It was also realized that the EMP initiated by a firm have a direct positive impact on the overall environmental performance of the firm. Research limitations/implications: There is the need for organizations to take steps to plan and implement EMP since it is likely to enhance their competitive operational performance as well as their overall environmental performance. Practical implications: The findings demonstrate the impact of EMP on competitive operational performance as well as on the overall environmental performance of firms. This is important as firms struggle with balancing investments in those practices against the perceived benefits that might be obtained from the practices. Originality/value: The work provides insights and adds to the literature in the area of EMP and firm performance by providing evidence from a developing country environment. This study is among the few that have investigated the impact of EMP on firm performance in developing country environments.